2001
DOI: 10.1016/s0006-3495(01)76053-5
|View full text |Cite
|
Sign up to set email alerts
|

Pulse EPR Detection of Lipid Exchange between Protein-Rich Raft and Bulk Domains in the Membrane: Methodology Development and Its Application to Studies of Influenza Viral Membrane

Abstract: A pulse saturation-recovery electron paramagnetic resonance (EPR) method has been developed that allows estimation of the exchange rates of a spin-labeled lipid between the bulk domain and the protein-rich membrane domain, in which the rate of collision between the spin label and molecular oxygen is reduced (slow-oxygen transport domain, or SLOT domain). It is based on the measurements of saturation-recovery signals of a lipid spin label as a function of concentrations of both molecular oxygen and the spin lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 59 publications
(100 reference statements)
5
110
1
Order By: Relevance
“…Single particle tracking experiments indicated that single glycosylphosphatidylinositolanchored proteins are organized in very small domains (Ͻ10 nm) with a short lifetime being in the order of 0.1 ms (52). This short transient stability is in agreement with electron spin resonance measurements revealing that spin-labeled lipids reside within a typical time of ϳ100 ns in rafts (53). Based on these characteristic properties of lipid domains and our estimates on the resolution of FLIM measurements (see above), our approach should be suitable to detect even nanometer-sized domains with very short stability.…”
Section: Flim Is Suitable To Detect Transient Small Lipid Domains-supporting
confidence: 86%
“…Single particle tracking experiments indicated that single glycosylphosphatidylinositolanchored proteins are organized in very small domains (Ͻ10 nm) with a short lifetime being in the order of 0.1 ms (52). This short transient stability is in agreement with electron spin resonance measurements revealing that spin-labeled lipids reside within a typical time of ϳ100 ns in rafts (53). Based on these characteristic properties of lipid domains and our estimates on the resolution of FLIM measurements (see above), our approach should be suitable to detect even nanometer-sized domains with very short stability.…”
Section: Flim Is Suitable To Detect Transient Small Lipid Domains-supporting
confidence: 86%
“…58 Moreover, it has been shown that viral assembly takes place within lipid rafts of the plasma membrane and that the viral envelope is enriched in lipid raft components. [59][60][61] Our data suggest that the calcium-induced microvesiculation and nanovesiculation of erythrocytes are also lipid raft-based processes, with stomatin and synexin being the major raft proteins, respectively. It remains to be determined whether the membrane-aggregating 38 and fusogenic 62,63 activities of synexin play a role in these processes, with sorcin being a modulator.…”
Section: Discussionmentioning
confidence: 73%
“…Small rafts can sometimes be stabilized to form larger platforms through proteinprotein and protein-lipid interactions." The dynamic character of rafts has also been shown in other studies [14][15][16]. Suzuki et al [15,16] discussed the possible role of dynamic raft microdomains in signal transduction in the plasma membrane.…”
Section: Introductionmentioning
confidence: 62%